Cadmium speciation and release kinetics in a paddy soil as affected by soil amendments and flooding-draining cycle. (1st January 2021) - Yan, Jiali; Fischel, Matthew; Chen, Hongping; Siebecker, Matthew G.; Wang, Peng; Zhao, Fang-Jie; Sparks, Donald L.
Abstract: Cadmium bioavailability in paddy soils is strongly affected by flooding-draining cycle. In this study, we used synchrotron-based X-ray absorption spectroscopy and a stirred-flow method to investigate the effects of flooding-draining and amendments of CaCO3 and CaSO4 on Cd speciation and release kinetics from a Cd-spiked paddy soil (total Cd concentration of 165 mg kg −1 ). Extended X-ray absorption fine structure analysis showed that Cd was predominantly bound to non-iron-clay minerals (e.g. Cd-kaolinite, Cd-illite, and Cd-montmorillonite, accounting for 60–100%) in the air-dried soil and 1- or 7-day flooded samples. After prolonged flooding (30 and 120 days), Cd-iron mineral complexes (e.g. Cd bound to ferrihydrite and goethite) became the predominant species (accounting for 52–100%). Stirred-flow kinetic analysis showed that both prolonged flooding and the amendments with CaCO3 and CaSO4 decreased the maximum amount and the rate coefficient of Cd release. However, the effect of prolonged flooding was reversed after a short period of draining, indicating that although Cd was immobilized during flooding, it became mobile rapidly after the soil was drained, possibly due to pH decrease and rapid oxidation of CdS. The effects of the amendments on Cd uptake in rice plants were tested in a pot experiment using the same paddy soil without Cd spiking (total Cd 2.1 mg kg −1 ). Amendment with CaCO3 and, to a lesser extent, CaSO4, decreased the Cd accumulation in two cultivars of rice. The combination of CaCO3 amendment and a low Cd accumulating cultivar was effective at limiting grain Cd concentration to below the 0.2 mg kg −1 limit. Graphical abstract: Image 1 Highlights: Soil amendments and flooding-draining cycle impact paddy soil Cd speciation and release kinetics. Cd bound to iron minerals predominated after long-term flooding. Cd immobilized during flooding became mobile rapidly after draining. CaCO3 amendment was effective at decreasing Cd accumulation in rice grain. Abstract : Capsule: Flooding changed cadmium speciation in a paddy soil and decreased Cd release kinetics. However, Cd immobilized during flooding became mobile rapidly after drainage.